IMPLEMENTASI KOMPETENSI KEPRIBADIAN GURU UNTUK PENGUATAN KARAKTER TOLERANSI DALAM PEMBELAJARAN SISWA - Yumri Yublince Anin; Yulius Mataputun; Albaiti Albaiti; Petrus Irianto; Robert Masreng; Urip Wahyudin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the implementation of teachers’ personality competence in strengthening students’ character of tolerance in the learning process, the supporting and inhibiting factors of its implementation, as well as its impact on students’ attitudes, the learning environment, and students’ social relationships at SD Negeri Yokobak, Lanny Jaya Regency, Papua Highlands Province. This research employed a qualitative approach using a case study design. Data collection techniques included in-depth interviews, observations, and documentation. The research informants consisted of the principal, teachers, students, and parents. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that teachers’ personality competence reflecting a stable, mature, wise, authoritative, and morally upright character has been concretely implemented in both classroom learning and school life. This implementation contributes to the development of students’ tolerant attitudes, the creation of a safe and inclusive learning environment, and the establishment of harmonious social relationships among students. The main supporting factors include teachers’ role modeling and consistency, support from the principal, and a school culture oriented toward tolerance values. Meanwhile, the inhibiting factors include limited facilities, lack of teacher training, differences in family backgrounds, and the socio-economic conditions of students’ environments. The conclusion of this study confirms that teachers’ personality competence plays a strategic role in strengthening students’ character of tolerance. These findings provide important implications for strengthening character education practices in primary schools and serve as a foundation for policy development and further research related to tolerance education in multicultural regions.